Genetic analysis in a female manifesting haemophilia B. Issue 829 (November 1994) - Palmer, S.; Standen, G. R.; Yates, P.; Oakhill, A.
Abstract : A 5 year old female child presented with a psoas haematoma as the first manifestation of haemophilia B. Molecular genetic studies were performed to investigate the inheritance of the disorder and the mechanisms by which females may express the haemophilia B phenotype are discussed.